1991
DOI: 10.1084/jem.173.2.519
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous growth and tumorigenicity induced by P40/interleukin 9 cDNA transfection of a mouse P40-dependent T cell line.

Abstract: To test the transforming potential of deregulated P40/Interleukin 9 expression, we transfected a mouse P40-dependent T cell line with P40 cDNA, and examined the tumorigenicity of the resulting transfectants. When the cells, which grew autonomously in vitro, were injected intraperitoneally or subcutaneously into syngeneic mice, a very high tumor incidence was observed with as few as 10(4) cells per inoculum. Animals died as a result of widespread dissemination of lymphomatous tissue to abdominal and thoracic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…36 Despite the lack of significant effects on freshly isolated T cells, 24,37 IL-9 induces significant proliferative effects on stimulated T cells. 23,24 Nonetheless, Renauld et al showed that only 7% of IL-9 transgenic mice develop T-cell thymic lymphomas. 38 Importantly, a subcarcinogenic dose of N-methyl-N-nitrosourea induced thymic lymphomas in all of the treated IL-9 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Despite the lack of significant effects on freshly isolated T cells, 24,37 IL-9 induces significant proliferative effects on stimulated T cells. 23,24 Nonetheless, Renauld et al showed that only 7% of IL-9 transgenic mice develop T-cell thymic lymphomas. 38 Importantly, a subcarcinogenic dose of N-methyl-N-nitrosourea induced thymic lymphomas in all of the treated IL-9 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…IL-9 is known to induce proliferation and antiapoptotic effects in T cells. [23][24][25] Previous studies showed that enforced expression of NPM-ALK in IL-9 transgenic mice induces widespread lymphoma. 26 The mechanism by which IL-9 promotes NPM-ALK activity is not known.…”
Section: Introductionmentioning
confidence: 99%
“…21 The progressive deregulation undergone by T cells during acquisition of IL-9 responsiveness is somewhat reminiscent of the multistep process leading to cell transformation. 22,23 Furthermore, the IL-9-responsive TS1 cell line could spontaneously give rise to growth factor (GF)-independent clones that were tumorigenic in vivo. 24 Even though there was no autocrine cytokine production in the supernatants of these GF-independent clones, they showed constitutive phosphorylation of JAK1, JAK3, STAT3, and STAT5 comparable to those induced by IL-9 stimulation in parental TS1 cells.…”
Section: W515kmentioning
confidence: 99%
“…The murine cell line TS1G6 was reported in detail earlier (Uyttenhove et al, 1991). In brief, an intraabdominal (IAb)-restricted, CD3ϩ, CD4ϩ T helper cell clone (TS1) derived from a C57Bl/6 mouse and specific for human keyhole limpet hemocyanin (KLH) was cultured without antigen and feeder cells, but in the presence of IL-9.…”
Section: Morphological and Immunohistochemical Characterization Of Tsmentioning
confidence: 99%